PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Alvina, Sufiyati (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study was to analyze the influence of profitability, liquidity, company size, and investment decisions on the value of the company in the utility, infrastructure, and transportation sector service companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 - 2017. used in this study using purposive sampling and 40 companies selected as samples. The technique for processing data in this journal uses multiple regression analysis with the help of IBM SPSS Statistics 25 and Microsoft Office 2013 programs. The results of this study indicate that liquidity and investment decisions have a significant effect on firm value, while firm profitability and size don’t significantly influence firm value.